Aspirin Minimized the Pro-Metastasis Effect of Sorafenib and Improved Survival by Up-Regulating HTATIP2 in Hepatocellular Carcinoma - Lu, Lu (Public Library of Science, 2013)
BACKGROUND & AIMS: We previously demonstrated the pro-metastasis effect of sorafenib in hepatocellular carcinoma (HCC), which is mediated by down-regulation of tumor suppressor HTATIP2. The aim of the present study was to determine whether aspirin minimizes this effect and improves survival. METHODS: The effects of sorafenib, aspirin, and combined sorafenib and aspirin were observed in HCCLM3 and HepG2 xenograft nude mice. Tumor growth, intrahepatic metastasis (IHM), lung metastasis, and survival were assessed. Polymerase chain reaction (PCR) array, real-time (RT)-PCR, and Western blotting were used to examine gene expression. The anti-invasion and anti-metastasis effects of aspirin were studied in HTATIP2-knockdown and HTATIP2-overexpressing HCC cell lines. The molecular mechanism of HTATIP2 regulation by aspirin was explored. RESULTS: Aspirin suppressed the pro-invasion and pro-metastasis effects of sorafenib in HCC and up-regulated HTATIP2 expression. Aspirin did not inhibit the proliferation of HCC cells, but it decreased the invasiveness of HCC with lower expression of HTATIP2 and increased expression of a set of markers, indicating a mesenchymal-to-epithelial transition in tumor cells. The up-regulation of HTATPI2 expression by aspirin is most likely mediated through inhibition of cyclooxygenase (COX) 2 expression. CONCLUSIONS: Aspirin minimized the pro-metastasis effect of sorafenib by up-regulating the tumor suppressor HTATIP2; this mechanism is mediated through inhibition of COX2.